Metformin carbon nanodots promote odontoblastic differentiation of dental pulp stem cells by pathway of autophagy - Lu, Jinjin; Li, Rui; Ni, Shilei; Xie, Yuandong; Liu, Xinchen; Zhang, Kai; Li, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
Human dental pulp stem cells (hDPSCs) have been a focus of pulp regeneration research because of their excellent odontogenic potential and availability. Applying the odontoblastic differentiation of hDPSCs to tooth regeneration has been challenging. Metformin-based carbon nanodots (MCDs) were synthesized and characterized to investigate their effects in vitro on odontoblastic hDPSC differentiation and the underlying mechanism. MCDs were synthesized by a hydrothermal treatment method and characterized using transmission electron microscopy (TEM), Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The biocompatibility and fluorescence properties of the MCDs in Dulbecco's modified Eagle's medium high-glucose culture medium and the in vitro odontogenic potential and related mechanism of the bioactive nanomaterial was explored. TEM images showed that MCDs were spherical in shape with a size of approximately 5.9 nm. MCDs showed biological safety in cell viability, apoptosis, and fluorescence labelling ability at a concentration up to 200 μg/mL in vitro. The presence of MCDs facilitated high-efficiency odontogenic differentiation of hDPSCs by promoting odontogenic gene and protein expression. Moreover, MCDs promoted odontoblastic hDPSC differentiation via autophagy. MCDs are capable of activating autophagy and enhancing the odontogenic differentiation of hDPSCs by upregulating odontoblast gene marker (DMP1, DSPP, RUNX2, and SP7) and protein (DSPP, DMP1) expression.